Reactions of hydrazones derived from oxamic acid thiohydrazides. (1st February 2017) - Volkova, Yulia A.; Chernoburova, Elena I.; Petrova, Albina S.; Shtil, Alexander A.; Zavarzin, Igor V.
GRAPHICAL ABSTRACT: ABSTRACT: This brief review describe the recent advances in using oxamic acid thiohydrazides as precursors for the formation of hydrazones intermediates from natural and synthetic compounds bearing a carbonyl group. These intermediates undergo a variety of synthetically useful transformations, which include nucleophilic addition and 6π-electrocyclic reactions to generate new heterocycles.